Potential fraud and its’ prevention in the implementation of national health insurance at Dadi Regional Hospita - Saru, Amaliah Amriani Amran; Arifin, Muhammad Alwy; Darmawansyah, Darmawansyah; Razak, Amran; Syafar, Muhammad; Rahmatia, Rahmatia (Intelektual Pustaka Media Utama, 2023)
The National Health Insurance program started running in Indonesia on January 1, 2014. Along with the increasing number of National Health Insurance participants and health facilities, more criticism has emerged from various parties, including from National Health Insurance providers regarding the alleged fraud. Fraud can have a negative effect on finances, the standard of medical care, and the perpetrator's reputation. This study's goal was to assess the likelihood that fraud may occur at Dadi Regional Hospital in Makassar, Indonesia. The study also explored the procedures and policies in place for preventing the fraud. This qualitative study employed phenomenological design. The results of the study show that there is a fraud prevention system at Dadi Regional Hospital in the form of policy and guideline formulation, a culture of prevention, implementation of quality control, and cost control. Even though they already have a prevention system in place, there is still some lack of information being disseminated about the fraud prevention team established. There are still frequent discrepancies between the diagnosis code input in the National Health Insurance system and the patient's diagnosis Hence, the Internal Monitoring Unit is still in the process of establishing a fraud prevention system